Acoustical enrichment during early postnatal development changes response properties of inferior colliculus neurons in rats. (16th September 2014) - Bureš, Zbyněk; Bartošová, Jolana; Lindovský, Jiří; Chumak, Tetyana; Popelář, Jiří; Syka, Josef
Abstract The structure and function of the auditory system may be influenced by acoustic stimulation, especially during the early postnatal period. This study explores the effects of an acoustically enriched environment applied during the third and fourth week of life on the responsiveness of inferior colliculus neurons in rats. The enrichment comprised a spectrally and temporally modulated complex sound reinforced with several target acoustic stimuli, one of which triggered a reward release. The exposure permanently influenced neuronal representation of the sound frequency and intensity, resulting in lower excitatory thresholds at neuronal characteristic frequency, an increased frequency selectivity, larger response magnitudes, steeper rate–intensity functions and an increased spontaneous activity. The effect was general and non‐specific, spanning the entire hearing range – no changes specific to the frequency band of the target stimuli were found. The alterations depended on the activity of animals during the enrichment – a higher activity of rats in the stimulus–reward paradigm led to more profound changes compared with the treatment when the stimulus–reward paradigm was not used. Furthermore, the exposure in early life led to permanent changes in response parameters, whereas the application of the same environment in adulthood influenced only a subset of the examined parameters and had only a temporary effect. These findings indicate that a rich and stimulating acoustic environment during early development, particularly when reinforced by positive feedback, may permanently affect signal processing in the subcortical auditory nuclei, including the excitatory thresholds of neurons and their frequency and intensity resolution.